Deconstructing Market Share Stagnation: The Dialectic of Regulation and the Dynamics of the Islamic Banking Ecosystem in Indonesia - Putri Ningsi; Revi Mariska; Tasya Amalia; Ayu Ariska (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2026)
This study examines the historical dynamics, regulatory architecture, and competitive landscape between Islamic and conventional banking in Indonesia. Utilizing a qualitative approach based on library research, this study dissects the operational ontology of both systems using secondary data from authoritative academic literature and official documents from financial institutions (OJK and Bank Indonesia). The analytical findings reveal that Islamic banking offers a superior paradigm of distributive justice through profit-and-loss sharing schemes and egalitarian partnership bonds, serving as an antithesis to the fixed interest rate regime in the conventional system. Although supported by a robust regulatory framework (Law No. 21 of 2008) and cross-institutional supervisory synergy, Islamic banking continues to face significant structural challenges. The dominance of conventional banks has led to a stagnation of the Islamic banking market share at approximately 10% of total national banking assets. The primary constraints stem from low specific Islamic financial literacy, technological infrastructure gaps, and limited-service product innovation. This study concludes that to disrupt market hegemony, Islamic banking entities require interventions that transcend theological sentiments, namely the acceleration of inclusive digital transformation, competitive financial product engineering, and affirmative policy support from the state to fortify its role within the national financial architecture